CEO duality and corporate performance: evidence in the Brazilian capital market - Costa, Yngrid Cabral Lima da; Martins, Orleans Silva (Revista de Administração da UFSM, 2019)
CEO duality is the practice in which the Chief Executive Officer (CEO) has both the presidency of the company as the chairman of its Board of Directors. The literature so far shows the positive and negative impact on organizational performance when this happens. The approach of the Agency theory suggests that these two functions should be exercised by different people. Therefore, this study aimed to verify the relationship between CEO duality and the corporate performance of companies listed on the Brazil Index (IBrX100) in the 2008 to 2013 period. The sample comprised 70 companies, totaling 420 observations in a balanced panel data. To investigate the relationship proposed by this study, two statistical strategies were used: the method of Ordinary Least Squares and Probit. The results showed that the duality did not affect the organizational performance when compared to the other explanatory variables. However, the performance was affected by the boar size and by the share concentration, as they were the only significant variables, meeting the findings of Daily and Dalton (1997) and Moscu (2013). This result confirms the premise that when duality exists, decisions generally tend to be centralized to avoid loss of control by managers.